Influence of alkoxy chain envelopes on the interfacial photoinduced processes in tetraarylporphyrin-sensitized solar cells. Issue 14 (18th March 2016) - Magnano, G.; Marinotto, D.; Cipolla, M. P.; Trifiletti, V.; Listorti, A.; Mussini, P. R.; Di Carlo, G.; Tessore, F.; Manca, M.; Orbelli Biroli, A.; Pizzotti, M.
Abstract : We have investigated the effect of the alkoxy chain length and nature on the reduction of dye-to-dye aggregation as well as on the enhancement of light harvesting capabilities. Abstract : The introduction of alkoxy chains in the molecular architecture of meso push–pull porphyrins is of paramount importance aiming at high performing dye-sensitized solar cells (DSSCs) based on these specific sensitizers. Recently, we have demonstrated that the same approach is fruitful even if it is applied to tetraarylporphyrins with an acceptor/anchoring substituent in the β-pyrrolic position. In particular, among the ortho – ortho, the ortho – para and the ortho -functionalization of the aryl rings with an octyloxy chain, we identified the latter as the most performing in the series, showing a good balance between the dye loading and the reduction of π–π aggregation. Herein, focusing our attention on the mono- ortho -functionalized molecular structure, we have investigated the effect of the alkoxy chain length and nature on the reduction of dye-to-dye aggregation as well as on the enhancement of light harvesting capabilities, finding an almost linear relationship between the device photon conversion efficiency (PCE) and the alkoxy chain length both in the presence and in the absence of a co-disaggregating agent.